THE EFFECT FROM APPLICATION OF STUDENT WORKSHEET BASED ON PROBLEM SOLVING IN ACHIEVING STUDENT'S CRITICAL THINKING SKILLS ON KINETIC THEORY OF GASES AND THERMODYNAMICS - Ade Aprilia; Yenni Darvina; Murtiani Murtiani; Wahyuni Satria Dewi (Universitas Negeri Padang, 2022)
The context of this research begins from learning that is still centered on teachers and students who are still difficult to solve high-level problems that can d evelop 21st century skills. One of the solution to researchers can help students in mastering the skills is using learning media the form of student worksheet based on problem solving. Therefore, this study aims to determine the effect of applying student worksheet based on problem solving for student’s critical thinking skills in kinetic theory of gases and thermodynamics. This type of research is quasi experimental research and use posttest only control design. This research involved two sample classes, namely experimental class and control class, with different learning patterns and student worksheets. The research tool is the final test of the essay questions. The assessment is based on indicators of critical thinking skills and descriptive data analysis techniques. Based on the data analysis completed, student’s' critical thinking skills improved after applying student worksheet based on problem solving during their learning. The data analysis results show that the value of tcount>ttable (3.78>2.00) indicates that there is a difference at a significance level of 0.05, with dk=n1+n2-1 as degrees of freedom. Therefore, it can be concluded that the application of student worksheet based on problem solving affects student’s acquisition of critical thinking skills in kinetic theory of gases and thermodynamics